GE_GERICHTE P/20367/2018 vom 15. April 2021 - GE Cour de justice (2021)
EXPERTISE MÉDICALE;SUSPENSION DE LA PROCÉDURE;PROCÉDURE ADMINISTRATIVE;PRINCIPE DE LA CÉLÉRITÉ | CPP.314; CPP.5; CPP.182; CPP.183.al1; CPP.184.al3